Examining the role of water vapor on small fatigue crack growth behavior in Ti-6242S using ultrasonic fatigue and scanning electron microscopy. (March 2022) - Geathers, J.; Torbet, C.J.; Jones, J.W.; Daly, S.
Highlights: We employ a combined in-situ ultrasonic fatigue scanning electron microscope system. We examine the effects of water vapor on small fatigue crack growth rates at 20 kHz. Fatigue crack growth rates increased with increasing water vapor pressure. A linear dependence of crack growth rate on water vapor pressure was observed. Environmental effects must be considered at 20 kHz for surface and sub-surface cracks. Abstract: The influence of water vapor on small fatigue crack growth rates in the near alpha titanium alloy Ti-6242S was investigated using a combined ultrasonic fatigue/environmental scanning electron microscope system (UF-SEM). Small fatigue cracks were grown at a cyclic frequency of 20 kHz in laboratory air, partial pressures of water vapor ranging from 65 to 1330 Pa, and vacuum (1.7 × 10 -4 Pa). Fatigue cracks grew at higher rates in all water vapor pressures investigated versus in vacuum, with a nearly identical growth rate observed in laboratory air and 1330 Pa water vapor. A linear dependence of small fatigue crack growth rate on water vapor pressure was observed that is consistent with a pressure dependent transport rate of water vapor molecules to the crack-tip. This work indicates that the amount of water vapor present in the environment (humidity) plays an important role in determining the fatigue life of Ti-6242S and must be accounted for even at very high cyclic frequencies, such as the 20 kHz cyclic frequency commonly employed in ultrasonic fatigue testing.